2009
DOI: 10.1038/sc.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 analog increases spinal cord blood flow at the point of compression during and after experimental spinal cord injury

Abstract: Study design: An in vivo study using a spinal cord compression model in rats. Objectives: To evaluate the effect of prostaglandin E1 (PGE1) on the change in thoracic spinal cord blood flow and on hind-limb motor function. Background: Until now, effect of PGE1 on spinal cord blood flow at the point of compression has not been tested. Methods: Our newly developed blood flow measurement system was a combination of a noncontacttype Laser Doppler system and a spinal cord compression device. The rat thoracic spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…bFGF stimulated the migration of cultured keratinocytes (27) and accelerated wound healing in a diabetic mouse model (9) and in pressure ulcers (10). PGE1 increased the intracellular cyclic AMP and reduced platelet aggregation (28,29) and was also found to increase tissue blood flow in an animal model (30). Furthermore, intravenous administration of PGE1 was effective in treating venous ulcers (31), diabetic skin ulcers (32) and skin ulcers stemming from collagen diseases (33).…”
Section: Discussionmentioning
confidence: 99%
“…bFGF stimulated the migration of cultured keratinocytes (27) and accelerated wound healing in a diabetic mouse model (9) and in pressure ulcers (10). PGE1 increased the intracellular cyclic AMP and reduced platelet aggregation (28,29) and was also found to increase tissue blood flow in an animal model (30). Furthermore, intravenous administration of PGE1 was effective in treating venous ulcers (31), diabetic skin ulcers (32) and skin ulcers stemming from collagen diseases (33).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism underlying PGE1's beneficial effect on ICH remains elusive. PGE1 may increase c-Fos and Myc proteins' expression and protect rat hippocampal cells from hypoxic injury (15,16), and prevent neuronal apoptosis in the rat spinal cord induced by sciatic nerve constriction (17,18). PGE1 may also effectively protect cortical neurons from glutamate cytotoxicity (19).…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E1 (PGE1)—a hormone-like substance, with antiischemic, antiinflammatory, 7 – 9 antiplatelet, and fibrinolytic properties 10 and tissue-protective effects (originates in the vascular endothelium)— 11 has been shown to increase perfusion in a rat model of cerebral ischemia 12 and in experimental studies of animals subjected to traumatic compression/decompression damage of the spine. 13 In a study on random pattern flaps in rabbits, increased distal perfusion was found up to 60 minutes after injection of PGE1. 14 …”
mentioning
confidence: 98%